Comparison Of Good Corporate Governance(GCG) Implementation Practices In Islamic Commercial Banks In Indonesia - Hendra Eka Saputra; Zul Ihsan (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2021)
Sharia Banking in Indonesia has a Sharia Supervisory Board that can monitor the operation of Sharia banks so that they are different from other banks. It is hoped that with this monitoring system the operation of corporate governance will be better. This study aims to explain the differences in the application of Good Corporate Governance (GCG) between Islamic banking in Indonesia. Sharia Bank is a bank whose application is different from conventional banks. Where one of the differences is the existence of a Sharia Supervisory Board which ensures bank activities are based on sharia. Then conducted a study of Islamic banks during 2014 to 2018. This research method uses descriptive analysis based on data that has been reported by each Islamic banking. The results of the survey showed that BCA Syariah and BSM received the highest rating among other sharia banks. This explanation shows that the implementation of corporate governance has been "very good" and has been in accordance with the stipulated provisions. BNIS, BRIS, Bukopin Syariah Bank, Mega Syariah Bank, Panin Syariah Bank, Victoria Syariah Bank, and Maybank Syariah, each ranked 2 (two). This means that the implementation of corporate governance goes "well". Interestingly, the Muamalat bank which has been the oldest BUS in Indonesia is ranked 3 (three). This means that the application of corporate governance is "good enough". Some notes on Muamalat's bank that must be corrected.